The retrospective study of cost analysis and short term outcome of laparoscopic and open anterior resection performed in Hospital Universiti Sains Malaysia - Mohamad, Mazwan (2017)
Introduction: Laparoscopic anterior resection of rectosigmoid cancer may improve short-term outcome. However only a few study have been done to evaluate the cost benefit of laparoscopic approach. In my study, I compared cost benefit and short-term outcomes of laparoscopic and open anterior resection of rectosigmoid cancer at Hospital University Sains Malaysia. This is the pilot study done at this centre for anterior resection surgery of rectosigmoid cancer. Methods: Between January 2000 and December 2014, a retrospective data of total 115 patients underwent anterior resection either laparoscopic or open technique base on the selection criteria. The data of patients were gained from patient’s medical records and entered in a data collection form. The non numerical demographic data analyzed using the Pearson’s chi square and the numerical data analysed usingIndependent T-test analysis. The primary outcome were shorterm outcome and cost analysis perioperative. Outcome parameters were: postoperative complication, length of hospital stay, surgical oncological margin. Cost-benefit analysis was based on hospital costs. The cost parameters were: length of stay, stapler, general anaesthesia, complication, dressing, intraoperative, post operative and total operative. These comparison involved both arms. Results: The mean age were 58 to 59 year old which the youngest aged 17 year old and the oldest aged 86 year old. No significant different in the gender for both groups of anterior resection (p 0.56). The major ethnic group was Malay in this study with percentage more than 90%. Almost majority of the laparoscopic approach of anterior resection were done in the stage I, II and III of rectosigmoid carcinoma. Meanwhile the open approached distributed almost in the entire stage of diseases (p 0.001). The laparoscopic or open approach gave no difference in the oncological resection margin outcome (p 0.345). Complication data showed that surgical site infection occurred in 2 patients (1.7%) for laparoscopic anterior resection (LAR) and 3 patients (2.6%) for open anterior resection (OAR). Two patients in the open anterior resection developed major early complication of anastomotic leak . However it was not statistically significant (p 0.333). The mean length of stay (LOS) was 11.41 days (SD, 3.65; range 6 to12 days) in the LAR group and 8.26 days ( SD, 1.22, range 7 to 25) in the OAR group. LAR group recorded shorter hospital stay with mean of 8.3 days while open AR recorded mean of 11.4 days (p 0.001). Cost analysis showed analytical significant in the LOS cost (p 0.001), intraoperative cost with metal/recycle trocar (p 0.001), total operative cost withmetal/recycle trocar (p 0.001). Meanwhile the remaining parameters were not significant in statistical analysis. Conclusions: Laparoscopic anterior resection in patient with rectal cancer resulted in an earlier postoperative recovery and similar shorterm outcome compare to the open anterior resection. Cost benefit analysis showed reduced charge in laparoscopic group if recycled laparoscopic trocar or usage metal trocar were used. Meanwhile there is a significant additional cost in laparoscopic if usage a new trocar for each operation slots.